2016
DOI: 10.1007/s00122-016-2768-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating haplotype-specific linkage maps in tetraploid species using SNP markers

Abstract: Key message Linkage mapping can help unravel the complexities of polyploid genomes. Here, we integrate haplotype-specific linkage maps in autotetraploid potato and explore the possibilities for mapping in other polyploid species. AbstractHigh-density linkage mapping in autopolyploid species has become possible in recent years given the increasing number of molecular markers now available through modern genotyping platforms. Such maps along with larger experimental populations are needed before we can obtain su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 37 publications
1
72
0
Order By: Relevance
“…We followed the mapping procedure as described for potato in Bourke et al . (), although it was not possible to associate homologue (simplex × nulliplex, or S × N) clusters into chromosomal groups on the basis of repulsion‐phase linkages due to more noise in the data. Instead, coupling linkages with duplex × nulliplex (D × N) markers were used to provide these associations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We followed the mapping procedure as described for potato in Bourke et al . (), although it was not possible to associate homologue (simplex × nulliplex, or S × N) clusters into chromosomal groups on the basis of repulsion‐phase linkages due to more noise in the data. Instead, coupling linkages with duplex × nulliplex (D × N) markers were used to provide these associations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, methods for creating integrated genetic maps in autotetraploid species using single nucleotide polymorphism (SNP) marker data have been developed (Hackett et al ., ; Bourke et al ., ). These methods offer the possibility of identifying repulsion‐linkages that can help reveal pairing behaviour.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been demonstrated that double reduction introduces some bias in recombination frequency estimates under a random bivalent model. This can be safely ignored if the rate of quadrivalent pairing is low (Bourke et al, 2015;Bourke et al, 2016).…”
Section: Linkage Analysis Under a Polysomic Modelmentioning
confidence: 99%
“…For several applications it is useful to integrate multiple genetic maps, for example to compare QTLs across populations, 22 to anchor genome assemblies, or to integrate haplotype specific linkage maps in autopolyploids (Bourke et al, 2016). 23…”
Section: Introduction 20mentioning
confidence: 99%